Optical gating of resonance fluorescence from a single germanium vacancy color center in diamond - Chen, Disheng (2019)
Scalable quantum photonic networks require coherent excitation of quantum emitters. However, many solid-state systems can undergo a transition to a dark shelving state that inhibits the resonance fluorescence. Here, we demonstrate that by a controlled gating using a weak nonresonant laser, the resonant fluorescence can be recovered and amplified for single germanium vacancies. Employing the gated resonance excitation, we achieve optically stable resonance fluorescence of germanium vacancy centers. Our results are pivotal for the deployment of diamond color centers as reliable building blocks for scalable solid-state quantum networks.